COVID-19 vaccine-associated myocarditis: Analysis of the suspected cases reported to the EudraVigilance and a systematic review of the published literature - Vikash Jaiswal; Dattatreya Mukherjee; Song Peng Ang; Tejasvi Kainth; Sidra Naz; Abhigan Babu Shrestha; Vibhor Agrawal; Saloni Mitra; Jia Ee Chia; Bernd Jilma; Mamas A. Mamas; Catherine Gebhard; et al. (International Journal of Cardiology: Heart & Vasculature, 2023)
Background: Myocarditis secondary to Coronavirus Disease 2019 (COVID-19) vaccination has been reported in the literature. Objective: This study aimed to characterize the reported cases of myocarditis after COVID-19 vaccination based on age, gender, doses, and vaccine type from published literature and the EudraVigilance database. Methods: We performed an analysis in the EudraVigilance database (until December 18, 2021) and a systematic review of published literature for reported cases of suspected myocarditis and pericarditis (until 30th June 2022) after the COVID-19 vaccination. Results: EudraVigilance database analysis revealed 16,514 reported cases of myocarditis or pericarditis due to the vaccination with COVID-19 vaccines. The cases of myo- or pericarditis were reported predominantly in the age group of 18–64 (n = 12,214), and in males with a male-to-female (M: F) ratio of 1.7:1. The mortality among myocarditis patients was low, with 128 deaths (2 cases per 10.000.000 administered doses) being reported. For the systematic review, 72 studies with 1026 cases of myocarditis due to the vaccination with COVID-19 vaccines were included. The analysis of published cases has revealed that the male gender was primarily affected with myocarditis post-COVID-vaccination. The median (IQR) age of the myocarditis cases was 24.6 [19.5–34.6] years, according to the systematic review of the literature. Myocarditis cases were most frequently published after the vaccination with m-RNA vaccines and after the second vaccination dose. The overall mortality of published cases was low (n = 5). Conclusion: Myocarditis is a rare serious adverse event associated with a COVID-19 vaccination. With early recognition and management, the prognosis of COVID-19 vaccine-induced myocarditis is favorable.